Biotechnology alternative for bovine supplementation by mango silage in the department of Atlántico, Colombia - Gómez-Peña, Gerardo Ramón; Guzmán-Nariño, Oscar Fabián; Burbano-Caicedo, Ilba (Revista Colombiana de Investigaciones Agroindustriales, 2020)
The aim of this research was to sustain conceptually and methodologically the importance of using mango waste through traditional biotechnology to obtain a supplement aimed at bovine feeding. The current state of the use of traditional biotechnology versus the recovery of mango waste, showed that, internationally, these wastes are mainly used in animal feed (23%), bioactive compounds (20%), the food industry and biofuels (17%). In Colombia, particularly in the Caribbean region, research focused on finding alternative solutions for animal nutrition, since these wastes were not being used efficiently. Regarding the Colombian regions whose economic activity is not livestock, the research options were aimed at the use of energy, biofuels, pharmaceuticals, cosmetics and nutrition. No patents were found related to the production of animal feed from mango residues. Then, a characterization of the mango residue was carried out through a proximal analysis to confirm the nutritional content in terms of protein, fiber and ash contrasting it with cane molasses and to be able to present a bovine supplementation option. Mango paste was found to have much higher nutritional values than cane molasses (7.19 for protein, 11.85 for raw fiber and 3.11 for ethereal extract). Today there are diverse possibilities to develop technological applications, such as, the silage of mango residues, thereby strengthening the competitiveness of this sector and its insertion in the international market. The mango agrifood chain is very important at the regional level and thinking about its development, in which biotechnology is one of the recurring technologies would allow to face a process of development of this territory, with social and economic implications.